What about America's homeless children?: hide and seek - Shane, Paul G. (Sage sourcebooks for the human services series, 1996)
Homeless children : who are they? -- Social and educational issues -- Health issues -- Social context of homelessness -- Unaccompanied children -- Families -- Babies -- Survivors -- Through the camera's lens -- Programs for unaccompanied youth and families -- Societal responses to homelessness -- Possible directions and conclusions